The Impact of ESG Factors on Company Share Prices in the European Energy Sector - Aneta Drab (Studia i Materiały)
ESG factors are increasingly becoming an inseparable part in company reports. Despite many difficulties connected with reporting of non-financial activities, there are more and more companies which undertake this difficult task each year. This kind of information is especially important for contemporary investors, who do not only look at the profit on a given investment, but pay more and more attention to the company’s image, methods of operation, approach to employees and the closer and farther environment. The hypothesis was as follows: the ESG factors have an increasing influence on stock prices. A panel study was used for the analysis. The study covered European energy companies which closed their financial year at the end of the calendar years 2010–2021. However, the results of the study did not reliably reflect the impact of ESG on the achieved rates of return because only in the last few years have they begun to gain significance. Previously, their impact was too weak to be shown in studies on larger samples.